Clinic management system - Noraini, Desa (2005)
A web based Ward Management System is a computerized system designed to meet the information needs of ward in hospital. Ward management system gives solution for nurses and doctors to complex and sensitive ward procedure.A research and analysis on the current system was done to get better understanding of the system.There is still some problem facin g ward management which requires numerous paper forms to store patient record and document.All this problem and manual task will be computerize and make data management easier.Expected result for the systems are provides easy operation and management for ward in hospital. Patient Medical Record also will be well manage and this system will automatically generate the vital sign and lab test graph, so this is make the nurse and doctor alert the changes for vital sign and lab test such as blood pressure. The Java Server Pages(JSP) being used as the programming language to develop the system and Oracle 9i as suitable database storage for ward management system.Rapid Application Development (RAD) is used as system development methodology.